Integrating network analysis and experimental validation to reveal the mitophagy-associated mechanism of Yiqi Huoxue (YQHX) prescription in the treatment of myocardial ischemia/reperfusion injury - Mingtai Chen; Guofu Zhong; Mengnan Liu; Hao He; Jie Zhou; Jianping Chen; Mingsheng Zhang; Qiang Liu; Guangdong Tong; Jienan Luan; Hua Zhou (Pharmacological Research, 2023)
Myocardial ischemia/reperfusion (I/R) injury is the main cause of increasing postischemic heart failure and currently there is no definite treatment for myocardial I/R injury. It has been suggested that oxidative stress-induced mitochondrial dysfunction plays an important role in the pathological development of myocardial I/R. In this study, Yiqi Huoxue (YQHX) prescription, as a kind of Chinese herbal formula, was developed and shown to alleviate I/R injury. Network analysis combined with ultrahigh-performance liquid chromatography-high resolution mass spectrometry expounded the active components of YQHX and revealed the mitophagy-regulation mechanism of YQHX treating I/R injury. In vivo experiments confirmed YQHX significantly alleviated I/R myocardial injury and relieved oxidative stress. In vitro experiments validated that YQHX could relieve hypoxia/reoxygenation injury and attenuate oxidative stress via improving the structure and function of mitochondria, which was strongly related to regulating mitophagy. In summary, this study demonstrated that YQHX, which could alleviate I/R injury via targeting mitophagy, might be a potential therapeutic strategy for myocardial I/R injury.